Enhancing Long Jump Abilities through Engklek and Lompat Tali: A Study on Traditional Games in Physical Education - Kristina, Putri Cicilia; Fahlifi, Rizal; Riyoko, Endie; Sugarwanto, Sugarwanto; Risma Putri, Siti Ayu (Jurnal Porkes, 2025)
The development of motor skills during childhood is critical for overall physical fitness and athletic performance. Traditional games, which are often culturally significant, play a vital role in enhancing these skills. This study aims to assess the impact of traditional games (e.g., Engklek and Lompat Tali) on the long jump performance of students at Elementary School 5 Kikim Timur. A comparative design was employed with a sample of 24 male students from Elementary School 5 Kikim Timur. The participants were randomly divided into two groups: Engklek and Lompat Tali, with 12 students in each group. Motor skills were assessed through standardized tests focusing on agility, coordination, explosive power, and speed. Long jump performance was evaluated based on four components: take-off, push, flight, and landing. Data analysis involved homogeneity and normality tests using SPSS version 23, followed by a one-way ANOVA test with a significance threshold of p < 0.05. Significant differences were found in long jump performance between the two groups. The incorporation of traditional games contributes to improved motor skills, enabling students to enhance their long-jump abilities effectively. Integrating traditional games into physical education programs offers a culturally relevant and engaging approach to improving motor skills and athletic performance. This study highlights the need for further research to explore the long-term benefits and potential applications of traditional games in various sports disciplines.